Assessment of Environmental Pollution in Mahadev Khola, Tarakeshwor Municipality - Adhikari, Pratima (Nepal Journal of Multidisciplinary Research, 2023)
One of the Small tributaries of the Bishnumati River is Mahadev Khola. It originates from Ale Danda, and downstream, it gets mixed with the Bishnumati River flowing from Tokha. It is 8.9 km in length and its elevation is 2000. The river's physio-chemical and biological characteristics were analyzed to know the river's pollution status. Primary data were collected from field observation and water sample analysis tests, and the secondary data were collected from the Tarkeshwor Municipality. Data analysis was done through MS-Excel. pH, ammonia, phosphate, chloride, hardness, iron, BOD5, and conductivity increase from upstream to downstream, whereas DO decreases. Temperature, turbidity, TS, TSS, and TDS were higher at the middle point than the other two, and coliform was found in the middle and exit points. Among the three segments of the river, the quality of the source point was good in terms of standards for drinking water. The middle and exit points were in medium and lousy condition, respectively.The principal causes of deteriorating water quality in Mahadev Khola are mainly the free and direct discharges of household and industrial wastes into the river and excessive mining of sand from the river bed. Since the quality of the river is deteriorating day by day, it’s the responsibility of the local government and the people to take immediate action for its conservation.